Isfahan and Istanbul in the early seventeenth century : Masjed-e Shah and Sultan Ahmed complexes - Gürkan Anar, Damla. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
This dissertation investigates the urban, architectural, and ceremonial formations of the Sultan Ahmed and Masjed-e Shah complexes, erected in early seventeenth century Istanbul and Isfahan by rival monarchs, Ahmed I (r.1603–1617) and Abbas I (r.1587–1629) respectively. This study conceptualizes these Friday mosque complexes as platforms manifesting their patrons’ comparable imperial agendas and analogous confessional policies through monumental architecture and theatrical rituality to different audiences, including each other’s representatives. It argues that besides corresponding religio-political flows at two rival courts, shared urbanistic, architectural, and aesthetic currents of the era played a significant part in their convergence as mosque complexes characterized by architectural grandeur, extravagance, decorative splendor, confessional ethos, and theatrical rituality. Combining the methods of architectural history with those of social and cultural history, this thesis delves into various textual and archival sources besides architectural evidence. It contributes to the comparative literature on the Safavid and Ottoman architectural cultures by presenting the first comprehensive comparative and connected analysis of two contemporary Friday mosque complexes erected in the Safavid and Ottoman capitals in the early seventeenth century.
Keywords: Turkey -- History -- Ahmed I, 1603-1617.; Abbas I, Shah of Iran, 1571-1629.; Sultanahmet Camii (Istanbul, Turkey); Masjed-e Shah (Isfahan, Iran); Architectural criticism.